Keterlibatan Ayah dalam Pengasuhan Anak Usia Dini - Andini Hardiningrum; Destita Shari; Jauharotur Rihlah; Afib Rulyansah (Institut Agama Islam Negeri Madura, 2024)
The presence of both parents in a child's life at an early age is very important in their growth and development. The complete presence of parents will stimulate aspects of the child's development optimally. Parents can share the same roles. Even though the division of roles and involvement has been divided, in fact the father's involvement is considered very minimal. There are still many fathers who think that men's main task is to work, thereby ignoring the role of fathers in optimizing aspects of children's development. In fact, involvement in raising children should be the responsibility of both parents, namely father and mother. According to the results of the May 11, 2021 edition of the Parapuan online daily survey, it was stated that in Indonesia the majority of husbands and wives share roles in caring for children with the highest percentage, namely 86.52%. This shows that the role of both parents is very important. Furthermore, other research shows that girls feel more close to their fathers with a percentage of around 67.05% compared to boys with a percentage of around 61.59%. Then, boys feel more close to their mothers with a percentage of 88.1% compared to girls whose percentage is around 85.25%. This shows that balancing parenting between father and mother is very important. This research uses a quantitative research method in the form of a survey conducted to obtain an overview of fathers' involvement in child care. The data analysis techniques used were interviews, distributing questionnaires, documentation and observation